Differential Gene Expression in Glioblastoma Defined by ADC Histogram Analysis: Relationship to Extracellular Matrix Molecules and Survival - Pope, W.B.; Mirsadraei, L.; Lai, A.; Eskin, A.; Qiao, J.; Kim, H.J.; Ellingson, B.; Nghiemphu, P.L.; Kharbanda, S.; Soriano, R.H.; Nelson, S.F.; Yong, W.; et al. (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: ADC histogram analysis can stratify outcomes in patients with GBM treated with bevacizumab. Therefore, we compared gene expression between high-versus-low ADC tumors to identify gene expression modules that could underlie this difference and impact patient prognosis. MATERIALS AND METHODS: Up-front bevacizumab-treated patients (N = 38) with newly diagnosed glioblastoma were analyzed by using an ADC histogram approach based on enhancing tumor. Using microarrays, we compared gene expression in high-versus-low ADC tumors in patients subsequently treated with bevacizumab. Tissue sections from a subset of tumors were stained for collagen and collagen-binding proteins. Progression-free and overall survival was determined by using Cox proportional hazard ratios and the Kaplan-Meier method with the log rank test. RESULTS: A total of 13 genes were expressed at 2-fold or greater levels in high- compared with low-ADC tumors at the P < .05 level. Of these, 6 encode for collagen or collagen-binding proteins. High gene expression for the collagen-binding protein decorin was associated with shorter survival (HR, 2.5; P = .03). The pattern and degree of collagen staining were highly variable in both high- and low-ADC tumors. CONCLUSIONS: High-ADC GBMs show greater levels of ECM protein gene expression compared with low-ADC GBMs. It is unclear whether this translates to the accumulation of higher levels of the encoded proteins. However, because ECM molecules could contribute to a proinvasive phenotype, this relationship merits further investigation. ADCLmean ADC (10−6 mm2/s) of the lower curve from the histogram analysisECMextracellular matrixGBMglioblastomaHRhazard ratioNIHNational Institutes of HealthRNAribonucleic acidRPArecursive partitioning analysisVEGFvascular endothelial growth factorVEGF-Avascular endothelial growth factor-A